Zoning of urban territorial spaces: evaluating socio-economic-ecological low-carbon development efficiency in Xuzhou, China - Liu, Pin; Ji, Xiang; Wang, Dong; Jiang, Deping; Hong, Xiaochun (Frontiers in Environmental Science, 2025)
As a critical spatial carrier for achieving the “dual carbon” strategic goals, measuring carbon emissions and assessing low-carbon development efficiency in urban territorial spaces are of great significance for promoting urban green and low-carbon transitions. This study focuses on urban territorial space as its research object, constructs a carbon accounting system for territorial spaces based on multi-source big data, and innovatively establishes a composite-dimensional low-carbon development efficiency evaluation model. It systematically evaluates the economic-social-ecological low-carbon development efficiency levels of various territorial spatial units and conducts a corresponding low-carbon zoning study. The findings indicate that the territorial space carbon accounting method developed in this study effectively supports the evaluation of composite-dimensional low-carbon development efficiency and provides a scientific methodological foundation for urban low-carbon zoning. The spatial structure of low-carbon development efficiency exhibits significant dimensional heterogeneity, with its characteristics conforming to regional socioeconomic development patterns. This reveals the inherent imbalance in low-carbon development across metropolitan territorial spaces. Based on the low-carbon development efficiency evaluations, territorial spatial units are classified into five types of low-carbon zones, including economically advantaged low-carbon zones, socially advantaged low-carbon zones, ecologically advantaged low-carbon zones, economically-socially advantaged low-carbon zones, and socially-ecologically advantaged low-carbon zones. The findings reveal significant spatial disparities in low-carbon development efficiency across Xuzhou City, necessitating differentiated low-carbon regulation strategies tailored to the carbon emission characteristics of each zone to foster low-carbon development in urban territorial spaces.